A new species of Rochefortia (Ehretiaceae, Boraginales) from the Lesser Antilles - Irimia, Ramona-Elena; Gottschling, Marc (Phytotaxa, 2015)
Taxonomic diversity of Neotropical Rochefortia is not completely assessed at present. We report the existence of a new species: Rochefortia barloventensis sp. nov., distributed across multiple islands of the Lesser Antilles. We provide a morphological description, a molecular diagnosis and a botanical illustration. Specimens belonging to the new species were previously assigned to Caribbean R. cuneata or to South American R. spinosa because of morphological similarity. Molecular sequence data shows a clear delimitation of the new species from all other species of Rochefortia justifying the recognition of a novel taxon.